Proliferative regeneration of zebrafish lateral line hair cells after different ototoxic insults. - Scott M Mackenzie; David W Raible (PLoS ONE)
Sensory hair cells in the zebrafish lateral line regenerate rapidly and completely after damage. Previous studies have used a variety of ototoxins to kill lateral line hair cells to study different phenomena including mechanisms of hair cell death and regeneration. We sought to directly compare these ototoxins to determine if they differentially affected the rate and amount of hair cell replacement. In addition, previous studies have found evidence of proliferative hair cell regeneration in zebrafish, but both proliferation and non-mitotic direct transdifferentiation have been observed during hair cell regeneration in the sensory epithelia of birds and amphibians. We sought to test whether a similar combination of regenerative mechanisms exist in the fish. We analyzed the time course of regeneration after treatment with different ototoxic compounds and also labeled dividing hair cell progenitors. Certain treatments, including cisplatin and higher concentrations of dissolved copper, significantly delayed regeneration by one or more days. However, cisplatin did not block all regeneration as observed previously in the chick basilar papilla. The particular ototoxin did not appear to affect the mechanism of regeneration, as we observed evidence of recent proliferation in the majority of new hair cells in all cases. Inhibiting proliferation with flubendazole blocked the production of new hair cells and prevented the accumulation of additional precursors, indicating that proliferation has a dominant role during regeneration of lateral line hair cells.